Immunization Against Vasoactive Intestinal Peptide and its Effects on Prolactin, Steroid, Luteinizing Hormone and Egg Production During Mid Laying Cycle in Punjab Brown (PB3 ) Birds - Reddy, I.J.; Kiran, G. Ravi; Mondal, S.K.; Anandan, S. (International Journal of Poultry Science, 2008)
Objective of the study is examine the effects of active immunization against chicken Vasoactive Intestinal Peptide (chVIP) on plasma prolactin (PRL) concentration, concentration of luteinizing hormone (LH) profile its interval and duration, Progesterone (P4), Estradiol (E2ß), intersequence pause days and egg production in birds during the later stages of egg production from 48-72 weeks of egg lay in PB3 birds. Twenty-four PB3 birds of same age group were divided into 2 groups of 12 in each. Birds in control group were administered s/c with placebo. Equal volume of chVIP immunogenic protein was administered to treated group from 17th week of age to 36 weeks of age at an interval of 4 weeks. Hormonal profiles of immunized and control birds were quantified at weekly intervals from 48th to 72nd weeks of age in both the groups for prolactin, LH, estradiol, progesterone. Egg production and pause days were recorded in both the groups. At 59th weeks of age, blood samples from chVIP immunized and control birds were obtained every 4 h for 48 h to study the surges of LH. In immunized PB3 birds (against ch VIP) plasma PRL concentration was lower (p<0.01) with high concentrations of E2ß, P4, LH and its 4 h LH surges in plasma. Significantly (p<0.01) higher egg production (13.62%) and less pause days were observed in chVIP immunized birds. It is mainly attributed due to low PRL concentration, associated with high concentrations of LH (with regular interval and duration of LH surges), E2ß and P4 concentration required for egg formation and subsequent ovulation. In conclusion, chVIP immunization advanced the LH surges, for release of matured oocyte, egg formation and egg lay enabled the birds to lay eggs at regular intervals due to active immunization against chVIP. Results indicate that control of chVIP may lead to more egg production with shorter duration of LH surges.